2017
DOI: 10.1111/eth.12622
|View full text |Cite
|
Sign up to set email alerts
|

Spread of false alarms in foraging flocks of house sparrows

Abstract: In group‐foraging species with no alarm signals, the sudden departure of neighbours can be used to inform the rest of the group about the detection of a threat. However, sudden departures are ambiguous because they can be triggered by factors unrelated to predator detection. We evaluated how animals react to the sudden departure of neighbours in groups of foraging house sparrows (Passer domesticus). We focussed on false alarms that occurred for no apparent reasons to us because predation attempts were not freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In another example, flocks of house sparrows (Passer domesticus) respond more quickly to social alarm cues (rapid departures) when in larger groups (Boujja-Miljour, Leighton & Beauchamp, 2017). Boujja-Miljour et al (2017) suggested that their predators may preferentially target larger flocks leading to higher vulnerability in larger groups, higher sensitivity to social cues, and hence to more false alarms. High vulnerability to predation means that the costs of an alarm response (see Section II.2.b) are offset by the risks associated with not responding to a true predator attack.…”
Section: (C) Vulnerability To Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example, flocks of house sparrows (Passer domesticus) respond more quickly to social alarm cues (rapid departures) when in larger groups (Boujja-Miljour, Leighton & Beauchamp, 2017). Boujja-Miljour et al (2017) suggested that their predators may preferentially target larger flocks leading to higher vulnerability in larger groups, higher sensitivity to social cues, and hence to more false alarms. High vulnerability to predation means that the costs of an alarm response (see Section II.2.b) are offset by the risks associated with not responding to a true predator attack.…”
Section: (C) Vulnerability To Attackmentioning
confidence: 99%
“…2B). In another example, flocks of house sparrows ( Passer domesticus ) respond more quickly to social alarm cues (rapid departures) when in larger groups (Boujja‐Miljour, Leighton & Beauchamp, 2017). Boujja‐Miljour et al .…”
Section: Misclassification Of Stimuli and False Alarms At The Individ...mentioning
confidence: 99%
“…Under predation risk, dynamic information about threats is transmitted from alarmed group members to naïve ones, a phenomenon that is commonly called collective detection (Lima 1990;Pays et al 2013). This process often takes place through evolved signals such as alarm calls, but social cues including sudden movements (Coleman 2008;Hingee and Magrath 2009;Boujja-Miljour et al 2017), fright responses (Chivers and Ferrari 2014;Cruz et al 2020) or changes in posture (Brown et al 1999;Pays et al 2013) have also been found to convey information about the presence of predators in animal collectives. Adjustments to the behaviour of others (also referred to as 'behavioural contagion'; Firth 2020) do not only affect individual fitness by increasing survival probabilities, but can also lead to the emergence of correlated behaviours and space use in many individuals and thus influence system-level functions (Goodale et al 2010;Gil et al 2018;Tóth 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Under predation risk, dynamic information about threats is transmitted from alarmed group members to naïve ones, a phenomenon that is commonly called collective detection (Lima 1990; Pays et al 2013). This process often takes place through evolved signals such as alarm calls, but social cues including sudden movements (Coleman 2008; Hingee and Magrath 2009; Boujja-Miljour et al 2017), fright responses (Chivers and Ferrari 2014; Cruz et al 2020), or changes in posture (Brown et al 1999; Pays et al 2013) have also been found to convey information about the presence of predators in animal collectives. Adjustments to the behaviour of others (also referred to as ‘behavioural contagion’; Firth 2020) do not only affect individual fitness by increasing survival probabilities, but can also lead to the emergence of correlated behaviours and space use in many individuals and thus influence system-level functions (Goodale et al 2010; Gil et al 2018; Tóth 2021).…”
Section: Introductionmentioning
confidence: 99%